Gonadal, body color, and genotoxic alterations in Lithobates catesbeianus tadpoles exposed to nonylphenol - Scaia, María Florencia [UNESP]; de Gregorio, Lara Salgueiro [UNESP]; Franco-Belussi, Lilian [UNESP]; Succi-Domingues, Maysa [UNESP]; de Oliveira, Classius [UNESP] (Springer Nature, 2019)
Endocrine disrupting chemicals are one of the most important factors contributing to worldwide amphibian decline. The 4-nonylphenol (NP) is a degradation product of several compounds, such as detergents and pesticides, affecting the aquatic environment. Here, we test whether treatment with NP has an effect on developing ovarian tissue, nuclear abnormalities in erythrocytes, and body darkness in pre-metamorphic tadpoles of the bullfrog Lithobates catesbeianus. Tadpoles were exposed for 14 days to three different concentrations of NP (1, 10, and 100 μg/L) besides the control group, which was maintained only with water. After determining body coloration, animals were euthanized and gonads and blood were collected and processed for histology and genotoxic analysis. Even though most animals were females, intersex tadpoles were observed in control and treated groups and there were no males in any group. The highest concentration of NP showed an increase in atretic oocytes, but the area corresponding to somatic compartment and early and late germ cells were not affected. Furthermore, all treated groups presented higher amount of nuclear abnormalities in erythrocytes and body darkening when compared with the control group. These results suggest that NP causes genetic damage and morphological alterations in L. catesbeianus tadpoles by disrupting oogenesis, inducing genotoxicity and increasing body coloration. Its effects on gonadal development could cause future impairments in reproduction, while its deleterious effects on genotoxicity and body pigmentation could be used as a biomarker of effect to this compound.
Keywords: Body pigmentation; Cellular abnormalities; Endocrine disrupting chemicals; Estrogenic compounds; Gonadal differentiation; Oogenesis